An elderly patient with depression and a suicide attempt during the COVID-19 pandemic: a case report - Mohd Salleh Sahimi, Hajar; Midin, Marhani; Lim, Jane Tze Yn; Anwar, Mohd Wafiy Ariffin; Abdul Samad, Farah Deena; Mohamad Kamal, Nurul Ain (Frontiers in Psychiatry, 2023)
Objective Elderly individuals are among the age groups with the highest risk of suicide. The coronavirus (COVID-19) pandemic forced isolation and resulted in an increased risk of depression, hopelessness, and perceived burdensomeness among the elderly, thereby increasing the risk of suicide. Methods This is a case report of an elderly single retired school principal with obsessive-compulsive personality traits who developed depression with psychotic symptoms after being isolated following the movement control order (MCO) during the COVID-19 pandemic. The social isolation led to feelings of loneliness and hopelessness. The patient’s depressive symptoms worsened after he developed physical illnesses, such as eye floaters, that affected his daily activities. This caused him to have suicidal ideation to the extent that he attempted suicide by ingesting 90 mL of pesticide. Two weeks prior to the attempt, he updated his will and asked his friend to keep it. After the suicide attempt, he vomited and had diarrhea and epigastric pain. He called his friend, who brought him to the hospital emergency room (ER). He was resuscitated and subsequently admitted to the intensive care unit (ICU). After being medically stabilized, he was transferred to the psychiatric ward, where further treatment was administered for his depression. His depressive symptoms and suicidal ideation improved after he was administered antidepressants and psychotherapy. Results The impact of the COVID pandemic has led to a surge in mental health issues such as anxiety and depression. The elderly are among the highest-risk groups of individuals to contract or die of COVID-19 infection, and they are also the most likely to develop mental health issues related to the pandemic. Furthermore, the risk of death by suicide is highest in this age group due to physical illness, social isolation, and the lack of a support system. This case also highlights the need for awareness of suicidal ideation screening among non-medical healthcare professionals and religious organizations to avoid the treatment gap. Conclusion It is essential to enhance suicide risk assessment and management among the elderly after the COVID-19 pandemic.